(untitled) (Iranian Journal of Kidney Diseases, 2023)
Introduction. Hypertension (HTN), also known as high blood pressure (BP), is a major global risk factor for cardiovascular and kidney diseases. Although annual BP screenings for children over three years of age are recommended, underdiagnosis of HTN in children is common. To address this issue, the American Academy of Pediatrics updated its guideline for screening and managing high BP in children in 2017, which can be cumbersome to implement in clinical practice due to the numerous cut-off points and tables. The purpose of our study is to design formulas to detect HTN in children based on the new Clinical Practice Guideline for screening and management of high BP in children and adolescents. Methods. In this research, we analyzed forty-eight cut-off points using the 90th percentile systolic and diastolic BPs for the fifth percentile height. The final mathematical model consisted of four formulas based on different ages and sex which in turn were rounded by 0.1 and 1.0 for both systolic and diastolic BPs. The formulas were further modified to be lower than the 95th percentile systolic BPs for the fifth percentile of height to minimize false negative results. Results. As evidenced by the tables included in this paper, except for a few exceptions, all rounded systolic and diastolic values for both sexes were equal to or lower than the 90th percentile. In a few cases where the cutoff points calculated by the formula were higher than the ones provided in the 2017 guideline, the differences were less than 2 mmHg. Conclusion. In this study to address the complexity of the routine guidelines, we present simplified formulas for screening children aged 1 to 12 years in figures and tables and recommend their use, particularly in office and emergency settings, as an easier-to-implement first step in screening for HTN in children. DOI: 10.52547/ijkd.7525